Improving cancer care locally: Study of a hospital affiliate network model. Issue 4 (13th December 2021) - Gao, Xiang; Schroeder, Mary C.; Lizarraga, Ingrid M.; Tolle, Cheri L.; Mullett, Timothy W.; Charlton, Mary E.
Abstract: Purpose: The University of Kentucky Markey Cancer Center Affiliate Network (MCCAN) increased access to high‐quality cancer care for patients treated in community hospitals across the state by leveraging the American College of Surgeons Commission on Cancer (CoC) standards to improve quality among its member sites. This study describes the network activities and services identified as most helpful or effective to its members, as well as the perceived value of joining MCCAN or pursing accreditation. Methods: An independent research team conducted in‐depth, semistructured interviews with 18 administrators and clinicians from 10 MCCAN hospitals in 2019. Interviews were transcribed and a thematic analysis was conducted. Findings: Network affiliation and CoC accreditation were perceived as helpful to improving quality of care. Having both clinician and administrative champions were key facilitators to achieving CoC standards and made mentoring of member sites a critical activity of the Network. Other components identified as valuable and/or key to the Network's success included providing access to specific CoC‐required clinical services (eg, genetic counseling); offering regular performance monitoring and individualized feedback; establishing a culture of quality improvement; and fostering trust within the Network with patient referrals (ie, sending patients back to their local hospital for ongoing care). Conclusions: Quality improvement in community cancer programs is challenging but several strategies were identified by members as valuable and effective. Efforts to disseminate the MCCAN model should focus on identifying the needs of community hospitals, implementing a quality monitoring system, and fostering site‐level champions who can be influential drivers of change.